Diplomasi Program Bipa (Bahasa Indonesia bagi Penutur Asing) melalui Kuliner Tradisional: Sebuah Studi Kasus di Universitas Ezzitouna, Tunisia - Widianto, Eko; Rahmania, Sofi Aulia (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2022)
Indonesian for Speakers of Other Languages (BIPA) has a diplomacy purpose. A cultural diplomacy is one of the main purposes in BIPA Program. This study was aimed to describe an Indonesian language and cultural diplomatic process in Tunisia, introduction of Indonesian for Speakers of Other Languages to the student by culinary, and introduction of Lumpia, Pukis, and Risoles to promote BIPA class in University of Ezzitouna, Tunisia. The data were collected via study case method. A researcher took a part in the even to collect and analyze the research data. A diplomatic mission to introduce language and culture of Indonesia could be showed by culinary. The culinary such as Lumpia, Pukis, and Risoles were popular in Indonesia. They also had a similar taste with Tunisian culinary. This way became one of the BIPA’s support to promote an Indonesian culture. A student in University of Ezzitouna interested to join BIPA class after trying to taste the culinary. Therefore, culinary had a good implication to support diplomatic mission to open BIPA class in the University of Ezzitouna, Tunisia.